Horticultural exports of developing countries: Issues under WTO regime - Deepak Shah (Colegio de Economistas de A Coru\~na, 2008)
This paper seeks to evaluate the present and future prospects of developing and developed countries in agricultural exports in general and in horticultural exports in particular. The study also evaluates the behaviour of international export prices for agricultural commodities, both for developing and developed nations. In general, this study provides an insight into the direction in which various developed and developing countries are heading for insofar as their agricultural and horticultural exports are concerned in the changed market conditions. The study has made a few major observations. First, the study shows decline in market share of developing countries' in world agricultural exports in the face of marginal increase in their market share in world fruits and vegetable (F&V) exports during the period between 1981 and 1997. Second, although the study shows lower market share of developing countries' in world F&V exports during the period between 1981 and 1997, the growth in F&V exports as proportion of total agricultural exports is noticed to be much faster for developing countries' as against the developed countries' during the same period. Third, though agricultural exports of Least Developed Countries (LDC) have grown only marginally between 1981 and 1997, the growth in their F&V exports is seen to have been tremendous, especially after the late eighties period. Similarly, Socialist Countries of Asia (SCA) and developing countries of Oceania have also shown sharp increases in their F&V exports after the late eighties period. Fourth, while except America, other Africa and Oceania, all the developing countries have shown decline in their market share in total F&V exports of Developing Market Economies (DME), Asia shows rise in its market share not only in agriculture but also in F&V exports of DME. Another major observation of this study is in terms of instabilities in export prices. The instabilities in export prices of agricultural commodities, including horticultural ones, are noticed to be more sharp for developing world as compared to developed world. The study, therefore, has categorically emphasized upon the fact that the future growth in horticulture production and trade, especially of developing world, will mainly depend on future price mechanism and also on the import demand of these high value crops in various regions of the world.
Keywords: 330